PERAN POLISI MASYARAKAT (POLMAS) DALAM MENANGANI PERBUATAN AKIBAT MINUM MINUMAN KERAS DI WILAYAH HUKUM POLRES SEMARANG - Rohadi Rohadi; Sri Kusriyah (UNISSULA Semarang, 2018)
Research titled Role of the Police Community policing (CBP) In Dealing Deeds Due to Drinking Alcohol In Semarang Police Jurisdiction.The method used in this research is a sociological juridical approach namely legal research study and research which is a reciprocal relationship between law and social institutions to another. The results showed that the role of the Community Police in dealing with acts from drinking liquor in the jurisdiction of Police Semarang focused on law enforcement by means of a non-penal pioneered by Bhabinkamtibmas in collaboration with community leaders. Shape optimization of track non penal in the sense of seeking common ground in the effort of deliberation and consensus that includes all the criteria in the agreement in the peace process outside the courts by using means of mediation or deliberation in achieving justice expected by the parties involved in the criminal law that is the perpetrator the crime of family and victims of crime family to find the best solutions that are approved and agreed by the litigants. Constraints faced by Community Police in dealing with acts from drinking liquor in Semarang Police Jurisdiction is the human resources inadequate, infrastructure, budget and finance, behavioral factor of habit with authorities or employers, and is not well understood and the culture ministry, yet fully have an understanding of the behavior as protectors and servants of the people and have not understood the Police professional code of ethics, limited ability to carry out the function of patrol officers, guard and Escort to the prevention of crime and the lack of ability to perform an analysis of crime, not communicative with the public, limited facilities, infrastructure supporting Samapta officer. In order to overcome the difficulties of handling acts from drinking liquor in the jurisdiction police station Semarang, Semarang Police Community Policing take steps as follows: Increasing the resources the Police in providing services in the field of law enforcement, emphasizing an understanding of the behavior of the police as protectors and servants of the people and the professional code of ethics police, improve the ability of officers to carry out the function of patrol, guard and escort to prevention of crime, to improve facilities, support infrastructure Bhabinkamtibmas officers, and conduct legal counseling to the community as well as the effects of drinking alcohol. Keywords: Community Police, Liquor